Takotsubo Cardiomyopathy in Dextrocardia with Situs Inversus - A. Ganes; L. Segan (Case Reports in Cardiology)
Takotsubo cardiomyopathy (TTC) is an acute reversible form of left ventricular (LV) systolic dysfunction extending beyond a coronary artery vascular territory usually due to physical or psychological stressors. Dextrocardia with situs inversus is a rare embryologic anomaly whereby the heart and aorta are mirrored on the contralateral side. We describe a case of a 93-year-old female with dextrocardia who presented with chest pain, atrial fibrillation with rapid ventricular response, and transient inferior ST elevation. Coronary angiography demonstrated an eccentric mid right coronary artery (RCA) lesion and apical ballooning consistent with concurrent takotsubo cardiomyopathy (TTC). To our knowledge, this is the first reported case of this dual pathology in a patient with dextrocardia, highlighting the procedural and diagnostic complexity in the setting of a rare anatomicvariant.